1995
DOI: 10.1080/14640749508401379
|View full text |Cite
|
Sign up to set email alerts
|

Is there a Relationship between Task Demand and Storage Space in Tests of Working Memory Capacity?

Abstract: This paper considers working memory capacity, critically examining the hypothesis that counting span (the ability to count arrays of objects and store count totals) reflects a trade-off in resources available for processing and short-term storage. Previous evidence interpreted as favouring this hypothesis has confounded task difficulty with counting time. Experiment 1 validated a manipulation of the attentional demands of counting in which target objects were differentiated from non-targets by either a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
230
3
16

Year Published

1997
1997
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(270 citation statements)
references
References 22 publications
21
230
3
16
Order By: Relevance
“…In all of these experiments, a higher number of retrievals:time ratio resulted in poorer recalls and lower working memory spans, even when the total duration of the intervening treatment was reduced (Experiments 5 and 6). This last result definitely rules out Towse and Hitch's (1995) task-switching model: Shorter treatments can lead to lower working memory spans. In accordance with our model, this fact suggests that participants switch their attention from processing to maintenance during the intervening activity and that the relative difficulty of this switching process determines what is called cognitive load.…”
Section: Discussion Of Experiments 4 -6mentioning
confidence: 84%
See 2 more Smart Citations
“…In all of these experiments, a higher number of retrievals:time ratio resulted in poorer recalls and lower working memory spans, even when the total duration of the intervening treatment was reduced (Experiments 5 and 6). This last result definitely rules out Towse and Hitch's (1995) task-switching model: Shorter treatments can lead to lower working memory spans. In accordance with our model, this fact suggests that participants switch their attention from processing to maintenance during the intervening activity and that the relative difficulty of this switching process determines what is called cognitive load.…”
Section: Discussion Of Experiments 4 -6mentioning
confidence: 84%
“…To test their cognitive load hypothesis against Towse and Hitch's (1995) memory decay hypothesis, Barrouillet and Camos compared Turner and Engle's (1989) operation span with the baba span while holding the total duration of both tasks constant. As predicted, the authors observed that the processing component involving a higher cognitive load (i.e., operation solving) led to lower recall performance and that the operation span was lower than the baba span.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Work along this line needs to flesh out in more detail how the resource limit is to be combined with the mechanisms of interference. (Baddeley et al, 1975;Schweickert & Boruff, 1986) Neo-Piagetian general resource model (Case et al, 1982) Feature model (Nairne, 1990) Limited-capacity trace-decay theory (Jensen, 1988;Salthouse, 1996) Multiple-resource model (Alloway et al, 2006;Logie, 2011) Interference model (Oberauer & Kliegl, 2001 Primacy model (Page & Norris, 1998) 3CAPS (Just & Carpenter, 1992) SOB (Lewandowsky & Farrell, 2008b) and SOB-CS (Oberauer, Lewandowsky, et al, 2012) Task-switching model (Towse & Hitch, 1995;Towse, Hitch, & Hutton, 2000) Slot model (Luck & Vogel, 2013;Cowan et al, 2012) Temporal-clustering-andsequencing model (Farrell, 2012) Computational phonological loop model (Burgess & Hitch, 1999 Resource models of visual WM Time-based resource-sharing model Camos et al, 2009) Note: Theories in the table were selected because they attribute the WM capacity limit unambiguously to decay, limited resources, or interference, respectively. Some theories of WM were not included because they combine two or three of the hypotheses, or make no clear assumptions about what causes the capacity limit.…”
Section: Resultsmentioning
confidence: 99%
“…However, other aspects of our results questioned our model. First, it appeared that Towse and Hitch's (1995) task-switching model is more appropriate to account for working memory in preschoolers than the TBRS model. Second, the three main sources of development of working memory-processing efficiency, storage ability, and amount of available attention-are probably, as Bayliss et al (2005) demonstrated, more independent than the TBRS model assumes.…”
Section: Discussionmentioning
confidence: 99%